The effects of MAC protocols on ad hoc on-demand distance vector (AODV) routing protocol - R. Badlishah, Ahmad; F., Hashim; Sabira, Khatun; B. M., Ali (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.